2007
DOI: 10.1200/jco.2007.11.5345
|View full text |Cite|
|
Sign up to set email alerts
|

Phase II Trial of Bevacizumab in Persistent or Recurrent Epithelial Ovarian Cancer or Primary Peritoneal Cancer: A Gynecologic Oncology Group Study

Abstract: Bevacizumab seems to be well tolerated and active in the second- and third-line treatment of patients with EOC/PPC and merits phase III investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
463
2
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 756 publications
(485 citation statements)
references
References 26 publications
13
463
2
7
Order By: Relevance
“…[7][8][9] Bevacizumab is a monoclonal antibody targeting vascular endothelial growth factor 10 and has activity against recurrent ovarian cancer. 11,12 Its role in adjuvant therapy is under investigation; the GOG-218 and ICON7 trials evaluated bevacizumab in combination with adjuvant IV carboplatin ϩ paclitaxel. 13,14 Both studies showed a small improvement in progression-free survival (PFS) among patients assigned to bevacizumab treatment.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%
“…[7][8][9] Bevacizumab is a monoclonal antibody targeting vascular endothelial growth factor 10 and has activity against recurrent ovarian cancer. 11,12 Its role in adjuvant therapy is under investigation; the GOG-218 and ICON7 trials evaluated bevacizumab in combination with adjuvant IV carboplatin ϩ paclitaxel. 13,14 Both studies showed a small improvement in progression-free survival (PFS) among patients assigned to bevacizumab treatment.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%
“…The GOG-170D trial showed that bevacizumab is an active drug in recurrent ovarian carcinoma, achieving a response rate of 21% and more importantly a median progression-free survival of 4.7 months, which was signifi cantly higher than previously observed in comparison to the median PFS obtained in historical GOG phase II trials with new drugs in recurrent ovarian carcinoma [7]. The toxicity of bevacizumab in this trial was not different from the expected hypertension and a low incidence of severe proteinuria or thrombotic events.…”
mentioning
confidence: 67%
“…These changes are hypothesized to result in improved delivery of oxygen, nutrients, and cytotoxic chemotherapy to the tumor [43]. Table 1 details notable phase 2 studies of anti-angiogenesis therapy in EOC [44][45][46][47][48][49][50][51][52][53][54]. Of the 6 molecules studied, 5 have been advanced to the phase 3 arena.…”
Section: Phase 2 Studiesmentioning
confidence: 99%
“…OCEANS, an industry sponsored trial, evaluated the efficacy and safety of bevacizumab in the treatment of patients with recurrent, platinum sensitive ovarian cancer [61]. This trial was initiated in response to GOG 170D, which indicated response to single agent bevacizumab in platinum sensitive and platinum refractory disease [44]. Rates of neutropenia and febrile neutropenia were similar in both arms.…”
Section: Phase 2 Studiesmentioning
confidence: 99%